2005
DOI: 10.1359/jbmr.050324
|View full text |Cite
|
Sign up to set email alerts
|

Thapsigargin Modulates Osteoclastogenesis Through the Regulation of RANKL-Induced Signaling Pathways and Reactive Oxygen Species Production

Abstract: ABSTRACT:The mechanism by which TG modulates osteoclast formation and apoptosis is not clear. In this study, we showed a biphasic effect of TG on osteoclast formation and apoptosis through the regulation of ROS production, caspase-3 activity, cytosolic Ca 2+ , and RANKL-induced activation of NF-B and AP-1 activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 49 publications
6
64
0
Order By: Relevance
“…Consistent with the observations, studies have demonstrated that DOX-mediated ROS production is reduced by the treatment of endothelial cells and H9c2 cells with an intracellular Ca 2+ chelator BAPTA (Kalivendi et al, 2001;2005). The increase of ROS generation is also observed in cardiomyocytes or spleen cells by treatment with Ca 2+ ionophore A23187 (Przygodzki et al, 2005) or thapsigargin (Yip et al, 2005), respectively. In addition, antioxidant properties of Ca 2+ channel blockers have been observed with in vivo and in vitro studies (Buyukokuroglu et al, 2001;Umemoto et al, 2004;Ysunari et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with the observations, studies have demonstrated that DOX-mediated ROS production is reduced by the treatment of endothelial cells and H9c2 cells with an intracellular Ca 2+ chelator BAPTA (Kalivendi et al, 2001;2005). The increase of ROS generation is also observed in cardiomyocytes or spleen cells by treatment with Ca 2+ ionophore A23187 (Przygodzki et al, 2005) or thapsigargin (Yip et al, 2005), respectively. In addition, antioxidant properties of Ca 2+ channel blockers have been observed with in vivo and in vitro studies (Buyukokuroglu et al, 2001;Umemoto et al, 2004;Ysunari et al, 2005).…”
Section: Discussionsupporting
confidence: 78%
“…[6][7][8] A series of recent reports have indicated that reactive oxygen species (ROS) play a critical role in osteoclast differentiation initiated by RANK-RANKL signals. [9][10][11][12][13] It has been already reported that several of the intracellular signals essential for osteoclast formation, including NFκB, c-Jun aminoterminal kinase, PI3-kinase, and p38 MAPK, are sensitive to ROS. [9][10][11] Osteoclast formation has been shown to depend on NFκB activation.…”
Section: Yudoh Et Al Dovepressmentioning
confidence: 99%
“…[9][10][11] Osteoclast formation has been shown to depend on NFκB activation. 7,9,13 It has been demonstrated that NFκB is a target for cellular activation by ROS 9,12 and that antioxidants suppress NFκB activation in osteoclasts. [13][14][15] Recent studies have clearly revealed that ROS mediates RANK-RANKL signaling in osteoclastogenesis.…”
Section: Yudoh Et Al Dovepressmentioning
confidence: 99%
“…To determine the effect of p62 wild-type and its UBA deletion mutant on RANKL-induced activation of NF-B and NFAT, RAW264.7 cells (5 ϫ 10 6 ) stably expressing EYFP-p62WT and EYFP-p62⌬UBA were transiently transfected with luciferase reporter construct 3 kb-Luc-SV40 as previously described 23,24 or with the luciferase reporter construct pNFAT-TA-Luc (BD Biosciences, San Jose, CA). Cells were plated in 24-well plates at a density of 1 ϫ 10 5 cells/well and treated with RANKL.…”
Section: Luciferase Reporter Gene Assay For the Nf-b And Nfat Activatmentioning
confidence: 99%
“…The importance of RANKL-induced activation on the cascades of mitogen-activated protein kinases, including extracellular signal-regulated kinase (ERK), in osteoclast differentiation and survival has been well documented. 24,27 To characterize better the involvement of p62 and its UBA domain in RANKL-signaling pathways and osteoclastogenesis, the role of p62WT and p62⌬UBA in RANKL-induced ERK phosphorylation was examined. Western blot analysis was performed using a specific antibody to the phosphorylated forms of ERK (ERK1/2).…”
Section: Overexpression Of Uba Domain Deletion Mutant Enhances Rankl-mentioning
confidence: 99%